(untitled) (Research, Society and Development, 2022)
The present study aimed to evaluate the microbiological and physical-chemical parameters of frozen fruit pulps commercialized in the city of Porto Franco, Maranhão State, Brazil. Six pulps of different fruits and components were selected and analyzed, being three acerola (Malpighia emarginata) and three cajá (Spondias mombin) pulps, in order to verify their adequacy to the norms and Standards of Identity and Quality (PIQ) stipulated by the Brazilian legislation. The physical-chemical parameters analyzed were pH, total titratable acidity, total soluble solids and ascorbic acid, and microbiological analyses were performed to evaluate the presence of total coliforms, mesophilic aerobic bacteria and Salmonella sp. In the microbiological analyses the presence of total coliforms, mesophilic aerobic bacteria and Salmonella sp. were not detected, indicating that the samples were in accordance with the current legislation, which certifies that the evaluated pulps are in adequate hygienic-sanitary conditions. The results obtained from the physical-chemical analysis revealed that all parameters evaluated were in accordance with the legislation, except the content of Total Soluble Solids for the three acerola samples, which showed results below the minimum value stipulated for acerola pulp by the legislation.